Sir John Cornforth Ac Cbe Frs: His Biosynthetic Work. (September 2015) - Purchase, Rupert; Hanson, James R.
Sir John Cornforth's work on the stereochemistry of enzyme reactions involved in the biosynthesis of squalene and cholesterol and in the formation and metabolism of a chiral methyl group in acetyl co-enzyme A, is reviewed.